A 6-GSamples/s multi-level decision feedback equalizer embedded in a 4-bit time-interleaved pipeline A - Varzaghani, A. (IEEE Journal of solid state circuits)
A 4-bit 6-GS/s pipeline A/D converter with 10-way time-interleaving is demonstrated in a 0.18-μm CMOS technology. The A/D converter is designed for a serial-link receiver and features an embedded adjustable single-tap DFE for channel equalization. The ISI subtraction of the DFE is performed at the output of each pipeline stage; hence the effective feedback delay requirement is relaxed by 6×. Code-overlapping of the 1.5-bit pipeline stage along with digital error correction is used to absorb and remove the remainder of the ISI. The measured A/D converter performance at 6-GSamples/s shows 22.5 dB of low-frequency input SNDR for the calibrated A/D converter with ±0.25 LSB and ±0.4 LSB of INL and DNL, respectively. The input capacitance is 170 fF for each A/D converter. The DFE tap coefficient is adjustable from 0 to 0.25 with 6-bits of programmable weight. With a DFE coefficient of 0.2, the measured DFE performance shows 2.5 dB of amplitude boosting for a 3-GHz input sinusoid. The 1.8×1.6 mm2 chip consumes 780 mW of power from a 1.8-V power supply.